ANALISIS PERILAKU SEKTOR PERTANIAN INDONESIA: APLIKASI VECTOR ERROR CORRECTION MODEL - Andi Irawan (Journal of Indonesian Economy and Business (JIEB), 2005)
The specific goals of this research are: Firstly, in the long run perspective, the goal is toanalyze impact of policy that inflating agriculture price to growth, employment, andinvestment in agriculture sector. Secondly, in the short run perspective, the goals are: (1) to analyze which economic blocks that have most producing instability to agriculture sector, (2) to analyze behaviour of inflation in agriculture sector and causality relationship both among output price and input prices and among input prices.Quantitative methods that are used in this study are Vector Error Correction Model,Johansen Cointegration Test, and Granger Causality Test. Data used in this research fromseveral sources such as Bank Indonesia, BPS Statistic, International Financial Statistic andCEIC data Company Limited, series data from first mountly of 1993 (1993:01) up to thelast mountly of 2002 (2002:12).In the agriculture sector, production (output) and capital are responsive to change inthe output price. This mean that inflating the output price effectively help generate outputand new investment in this sector. Nevertheless because shock in price can be source ofinstability to agriculture sector, so government should becarefully apply policies that caninflating the price in agriculture. To solve unemployment problem in agriculture sector,government should apply cost strategy such as subsidy policy of input price.Keywords: Instabilitas, Pergerakan Harga, Employment, Investasi, Sektor Pertanian,Vector Error Correction Model, Johansen Cointegration Test and Granger Causality Test